BUSINESS DEVELOPMENT STRATEGY TO IMPROVE COMPETITIVENESS IN ANTI-AGING CLINIC USING SWOT APPROACH ANALYSIS AND BUSINESS MODEL CANVAS (BMC) APPROACH - Hani Surjati; Maya Malinda; Benny Budiawan Tjandrasa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Elderly individuals have a substantial risk of suffering from chronic diseases that require high medical costs, both financially and in terms of time needed. It is important to pay attention to the quality of life of the elderly to reduce the burden of dependency. PT X has opened an Anti-Aging Clinic with the aim of providing services in preventing the decline in cell quality (anti-aging) to enhance the productive activities of the elderly. The main aim of this research is to analyze the SWOT followed by Business Model Canvas (BMC) and Value Proposition Canvas (VPC) analysis. The research method used is descriptive with a qualitative approach, and the data analysis technique uses SWOT including IFAS and EFAS, BMC analysis, and VPC. Data collection techniques include observation with documentary studies and secondary data. The Anti-Aging Clinic is in a hold and maintain position. The results serve as the basis for BMC mapping and VPC determination, especially in improving products and services. From its implementation, key activities are the main key to the clinic's management process that needs to be strengthened through market penetration and product development processes.